EXPERT SYSTEM FOR DIAGNOSING DISEASE UROLOGY TYPE SYSTEM IN HUMAN URINARY - Dina Herlina; Sahni D. Purba. Skom. MM (Jurnal Sistem Informasi, 2000)
Writing is about the ability of a computer system (expert system) in helping a doctorby using reasoning resembles an expert in the field to diagnose urological diseases inhumans. This expert system will ask certain questions, diagnosing problems, andultimately recommend a solution based on the facts and experiences that havehappened before that has been incorporated into database. So that later when anexpert was dead so his knowledge and experience will still be able to be used byothers by using an expert system.